Traumatic brain injury - Bernet, Bob.; Quiett, Bill.; Health & Science Television Network; Trinity Workplace Learning (TWL) Knowledge Group . [Firm] (Carrolton, TX : Trinity Workplace Learning Knowledge Group ; Health & Science Television Network, 2007)
Healthcare professionals must be able to properly recognize and assess the signs of a traumatic brain injury. Early recognition and treatment of an extreme brain injury could reduce immediate trauma and future complications. This activity looks at common brain injury findings after a traumatic event, in order to identify basic life support assessment and treatment modalities. Also discussed is the human cost for victims who must cope with a traumatic breain injury.--Container.
"Shape the future"--videodisc label.
Hosted by Bob Bernet.
DVD
Closed-captioned.
Keywords: Brain -- wounds and injuries -- patients -- rehabilitation; Brain damage; Brain -- wounds and injuries -- physical therapy -- long term care; Video recordings for the hearing impaired